Real-Time PCR for Simultaneous Detection and Quantification of Borrelia burgdorferi in Field-Collected Ixodes scapularis Ticks from the Northeastern United States - Wang, Guiqing (American Society for Microbiology, 2003)
The density of spirochetes in field-collected or experimentally infected ticks is estimated mainly by assays based on microscopy. In this study, a real-time quantitative PCR (qPCR) protocol targeting the Borrelia burgdorferi-specific recA gene was adapted for use with a Lightcycler for rapid detection and quantification of the Lyme disease spirochete, B. burgdorferi, in field-collected Ixodes scapularis ticks. The sensitivity of qPCR for detection of B. burgdorferi DNA in infected ticks was comparable to that of a well-established nested PCR targeting the 16S-23S rRNA spacer. Of the 498 I. scapularis ticks collected from four northeastern states (Rhode Island, Connecticut, New York, and New Jersey), 91 of 438 (20.7%) nymphal ticks and 15 of 60 (25.0%) adult ticks were positive by qPCR assay. The number of spirochetes in individual ticks varied from 25 to 197,200 with a mean of 1,964 spirochetes per nymphal tick and a mean of 5,351 spirochetes per adult tick. No significant differences were found in the mean numbers of spirochetes counted either in nymphal ticks collected at different locations in these four states (P = 0.23 by one-way analysis of variance test) or in ticks infected with the three distinct ribosomal spacer restriction fragment length polymorphism types of B. burgdorferi (P = 0.39). A high degree of spirochete aggregation among infected ticks (variance-to-mean ratio of 24,877; moment estimate of k = 0.279) was observed. From the frequency distribution data and previously published transmission studies, we estimated that a minimum of 300 organisms may be required in a host-seeking nymphal tick to be able to transmit infection to mice while feeding on mice. These data indicate that real-time qPCR is a reliable approach for simultaneous detection and quantification of B. burgdorferi infection in field-collected ticks and can be used for ecological and epidemiological surveillance of Lyme disease spirochetes.